Estudio de factibilidad para la creación de una empresa transformadora de plástico a fibra textil en Boyacá (2022)
In the subsequent research work, the focus was on making the feasibility for the creation of a company that transforms plastic (PET) into textile thread in the department of Boyacá, where the research was carried out from the pollution generated by plastic to our ecosystem and see this problem as an opportunity to improve both the environment and economically.